Effect of Rotor’s Aspect Ratio and Casing Inlet/Outlet Geometry on the Efficiency of a Rotor-Casing Assembly - Abu-Hijleh, Bassam (2006)
Computational fluid dynamics (CFD) simulation was used to study the effect of modifying the inlet and outlet of an elliptical rotor-casing assembly at two different rotor aspect ratios. The simulations were carried at different inlet velocities and rotor angular speeds. The flow field results were used to ascertain the changes in the efficiency of the rotor-casing assembly. The focus was on inlet pressure, maximum velocity, and maximum turbulence values. Entropy calculations were also used to evaluate the impact of the different configurations on the overall thermodynamic efficiency of the rotor-casing assembly. The results show the use of fillets has several advantages, especially when using high aspect-ratio rotors at high rpm values.